2017
DOI: 10.1002/hpm.2478
|View full text |Cite
|
Sign up to set email alerts
|

Ageing in India: Financial hardship from health expenditures

Abstract: India's rapidly ageing population raises concerns about the burden of health care payments among older individuals who may have both limited income and greater health care needs. Using a nationally representative household survey, we investigate the association between age and financial hardship due to health expenditures. We find that both the probability of experiencing health problems and mean total out-of-pocket health expenditures increase with age. Second, the probability of households experiencing catas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…Comparing the result of the present study with the past studies we found that inpatient health expenditure incurred by the elderly also escalates over time. Using NSS 71st round data, a study found 49 that the mean inpatient expenditure incurred by older adults (80–89 years) is almost INR 3497 in 2014, whereas the present study estimated that the mean combined inpatient expenditure (private + public) for a single episode of illness is nearly INR 12,050 indicating an almost threefold increase in inpatient health expenditure incurred by elderly, especially the oldest‐old group, over 4 years.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Comparing the result of the present study with the past studies we found that inpatient health expenditure incurred by the elderly also escalates over time. Using NSS 71st round data, a study found 49 that the mean inpatient expenditure incurred by older adults (80–89 years) is almost INR 3497 in 2014, whereas the present study estimated that the mean combined inpatient expenditure (private + public) for a single episode of illness is nearly INR 12,050 indicating an almost threefold increase in inpatient health expenditure incurred by elderly, especially the oldest‐old group, over 4 years.…”
Section: Discussioncontrasting
confidence: 72%
“…Comparing the result of the present study with the past studies we found that inpatient health expenditure incurred by the elderly also escalates over time. Using NSS 71st round data, a study found 49 Hence there is no doubt that the ageing population should be protected against impoverishment due to healthcare expenditure. In this context, it is worth mentioning that the National Programme for Health Care of the Elderly (NPHCE) happens to be the only comprehensive healthcare programme introduced for the elderly in India.…”
Section: Discussionmentioning
confidence: 99%
“…Following Sen’s theory, the present study attempts to empirically test the role of social position in determining the difference between SRH and actual health status among the elderly individuals (60 years and above) of India. Old health burden not only increases in the advanced ages (Lee et al , 2018) in India. The majority of the country's aged people experience deprivation (Chambers, 1995) and intensive old-age impoverishment (Pal and Palacios, 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Ageing populations have become the largest group of patients occupying hospital beds in the United States, the United Kingdom, Germany, Canada, and even in a few Latin American countries . Apart from Japan, South Korea, Singapore, India, and Taiwan are facing the phenomenon. However, the phenomenon is uncommon among other Asian countries because of their less developed economies and imperfect medical insurance systems.…”
Section: Literature Reviewmentioning
confidence: 99%